2017
DOI: 10.21088/ijde.0974.6099.10217.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries Prevalence in Sudanese Preschool Children

Abstract: Introduction: Dental caries is one of the most important global oral health problems. The distribution and severity vary in different parts of the world. This study aimed to determine the caries prevalence among a sample of preschool children and to assess the relation between maternal variables (age, educational level, occupation and family size) and the dental caries status of their preschool children. Subjects and Methods: A cross-sectional pre-school based study for 419 preschool children aged 3-5 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Personal hygiene can be assessed by the length, cleanliness and color of nails [17]. Previous study used nail hygiene examination to determine individual hygiene [18].…”
Section: Discussionmentioning
confidence: 99%
“…Personal hygiene can be assessed by the length, cleanliness and color of nails [17]. Previous study used nail hygiene examination to determine individual hygiene [18].…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso, Mazza et al [16] recorded a prevalence rate of 16.6% and in Nigeria, Folayan et al [17] reported an ECC prevalence rate of 6.6%. Higher but inconsistent prevalence rates were documented in Sudan (52.4% [18] and 71.4% [19]), whereas in Uganda, 64% of 3-5-year-old children had ECC [20].…”
Section: African Countries Have Also Shown Varying Prevalence Of Eccmentioning
confidence: 89%
“…African countries have also shown varying prevalence of ECC: In Burkina Faso, Mazza et al [ 16 ] recorded a prevalence rate of 16.6% and in Nigeria, Folayan et al [ 17 ] reported an ECC prevalence rate of 6.6%. Higher but inconsistent prevalence rates were documented in Sudan (52.4% [ 18 ] and 71.4% [ 19 ]), whereas in Uganda, 64% of 3-5-year-old children had ECC [ 20 ].…”
Section: Introductionmentioning
confidence: 99%